Achievement of Right Ventricular Pacing by Use of a Long Guiding Catheter in a Hemodialysis Patient Presenting Significant Tortuosity of Vasculature. (5th April 2011) - Dilaveris, Polychronis; Sideris, Skevos; Vaina, Sofia; Gatzoulis, Konstantinos; Stefanadis, Christodoulos
Abstract : Increased vascular calcification and tortuosity are rather common in end-stage renal failure patients who are on hemodialysis. It renders manipulation of catheters and performance of percutaneous transluminal interventions more difficult than expected. Such vascular alterations may be evident in large veins and pose significant difficulties in placement of pacing leads as shown in our case. To overcome such difficulties, we demonstrated in this patient case that long guiding catheters may be of particular value.